Tuning the organelle-imaging specificity of an aggregation-induced emission luminogen with reversible mechanochromism by ionization. Issue 20 (15th August 2022) - Yang, Xinzhe; Hu, Peiyu; Zhuang, Zeyan; Huang, Zixuan; Huang, Kaihang; Yin, Li; Wang, Qian; Luo, Suilian; Shi, Guang; Chen, Ling; Xu, Bingjia; Qin, Anjun
Abstract : Two organic luminogens with aggregation-induced emission properties have been developed and their emission colors are switchable under external stimuli. In addition, they can selectively image lipid droplets and mitochondria, respectively. Abstract : Realizing the bioimaging of different organelles usually requires organic luminophores with distinct molecular structures through a complicated chemical synthesis, which is tedious and time-consuming. Herein, an aggregation-induced emission luminogen (AIEgen) PNOy with a twisted molecular structure was prepared by employing tetraphenylethylene as the electron donor and phenylacrylonitrile-quinoline as the electron acceptor. It was found that PNOy showed a bathochromic shift of 41 nm in emission maximum under the stimulation of mechanical force. Concurrently, it could be used as a bioprobe with high specificity and biocompatibility to enable fluorescence imaging of lipid droplets (LDs) in cells. After the ionization and introduction of hexafluorophosphate as a counter ion, the resulting AIEgen PNO presented a much better stimulus-responsive performance, exhibiting a variation of 104 nm in emission maximum under the stimuli of mechanical force and acetone vapor. More impressively, PNO could be used for mitochondrial imaging with good membrane permeability and cell viability. This study demonstrates a helpful and straightforward approach to develop new bioimaging agents for different organelles and provides smart organic luminogens for innovative applications in sensing and anti-counterfeiting.